Powerful Plant Antioxidants: A New Biosustainable Approach to the Production of Rosmarinic Acid - Khojasteh, Abbas (Antioxidants (Basel), 2020)
Modern lifestyle factors, such as physical inactivity, obesity, smoking, and exposure to environmental pollution, induce excessive generation of free radicals and reactive oxygen species (ROS) in the body. These by-products of oxygen metabolism play a key role in the development of various human diseases such as cancer, diabetes, heart failure, brain damage, muscle problems, premature aging, eye injuries, and a weakened immune system. Synthetic and natural antioxidants, which act as free radical scavengers, are widely used in the food and beverage industries. The toxicity and carcinogenic effects of some synthetic antioxidants have generated interest in natural alternatives, especially plant-derived polyphenols (e.g., phenolic acids, flavonoids, stilbenes, tannins, coumarins, lignins, lignans, quinines, curcuminoids, chalcones, and essential oil terpenoids). This review focuses on the well-known phenolic antioxidant rosmarinic acid (RA), an ester of caffeic acid and (R)-(+)-3-(3,4-dihydroxyphenyl) lactic acid, describing its wide distribution in thirty-nine plant families and the potential productivity of plant sources. A botanical and phytochemical description is provided of a new rich source of RA, Satureja khuzistanica Jamzad (Lamiaceae). Recently reported approaches to the biotechnological production of RA are summarized, highlighting the establishment of cell suspension cultures of S. khuzistanica as an RA chemical biofactory.